2016
DOI: 10.1111/jog.13201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin‐1β and lipoxin A4 in human endometriotic stromal cells: Proteomic analysis

Abstract: Aim: Lipoxin A 4 (LXA 4 ) can function as an endogenous 'breaking signal' in inflammation and plays an important role in the progression of endometriosis. The proteome responses to interleukin-1β (IL-1β) or LXA 4 in human endometriotic stromal cells (ESC) are not well understood. Methods: In this study, primary ESC were cultured from ovarian endometriosis tissue. Three groups were established: the control group; the IL-1β stimulation group; and the IL-1β and LXA 4 incubation group. Proteins were assessed on 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In these studies, patients were at least 3–6 months without hormonal or anti-inflammatory treatment. ESCs were treated in cell culture with the mediator under investigation, and the evaluation was carried out through several types of laboratory analysis [ 7 , 19 , 30 , 31 , 33 , 34 , 35 ]. Rasheed et al analyzed in vitro halogenic stem cells by adding serum from patients diagnosed with endometriosis to evaluate cell differentiation and the expression of ANXA1 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, patients were at least 3–6 months without hormonal or anti-inflammatory treatment. ESCs were treated in cell culture with the mediator under investigation, and the evaluation was carried out through several types of laboratory analysis [ 7 , 19 , 30 , 31 , 33 , 34 , 35 ]. Rasheed et al analyzed in vitro halogenic stem cells by adding serum from patients diagnosed with endometriosis to evaluate cell differentiation and the expression of ANXA1 [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further, LXA4 inhibited COX-2 expression induced by IL-1β in ESCs through the FPR2/ALX modulation. According to Wu et al in proteomic analysis, LXA4 can suppress proteins that facilitate IL-1β-induced migration and invasion in ESC [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-α) also belongs to the group of pro-inflammatory cytokines. Several studies have shown that its serum concentration in patients with endometriosis may be elevated [ 93 ]. The development and progression of endometriosis is also influenced by interactions between the two groups of cytokines.…”
Section: The Importance Of Disorders Of Immune Homeostasis In the Pat...mentioning
confidence: 99%